A Recent Update: Molecular Mechanism of Kombucha as A Probiotic for Obesity Management - Nisa, Zulfia Rosyidatun; Jusup, Sinu Andhi; Yudhani, Ratih Dewi (Global Health Science Group, 2024)
The prevalence of obesity has continued to increase in the past decade which has an impact on several metabolic disorders in the body. Various efforts are made to reduce and overcome the effects of obesity such as pharmacological therapy. In addition, using natural ingredients such as probiotics is optimized to minimize the effects caused. The balance of gut microbiota has an important role in helping to improve dysbiosis, inflammation, and fatty liver in obesity. Method: This review used the scoping review necessary to collect and summarize scientific data as well as guide future investigations with the provision that articles are up to the last 10 years (2014) for kombucha as a drink rich in probiotics that could have potential as a natural therapy for obesity management. Results: A total of 244 articles were collected and 11 articles met the inclusion criteria. Conclusion: kombucha has beneficial effects and has the potential to improve obesity conditions from a variety of mechanisms.